If \(p \iff q\), then \(\Pr(p) = \Pr(q)\).
See: biconditional
Proof. If \(p \iff q\), then \(p \lor \lnot q\) is a tautology per
\[\begin{array}{cc|c|l} p & q & p \iff q & p \lor \lnot q \\ \hline 0 & 0 & \boxed{1} & 0 \lor \lnot 0 = 0 \lor 1 = \boxed{1} \\ 0 & 1 & 0 & \cdots \\ 1 & 0 & 0 & \cdots \\ 1 & 1 & \boxed{1} & 1 \lor \lnot 1 = 1 \lor 0 = \boxed{1} \> , \end{array} \]
and \(p\) is mutually exclusive with \(\lnot q\) per
\[\begin{array}{cc|c|l} p & q & p \iff q & \lnot q \\ \hline \boxed{0} & 0 & 1 & \boxed{1} \\ 0 & 1 & 0 & \cdots \\ 1 & 0 & 0 & \cdots \\ \boxed{1} & 1 & 1 & \boxed{0} \> , \\ \end{array} \]
so, we have
\[\begin{align*} \Pr(p \lor \lnot q) & = 1 && \text{per axiom 2} \\ \Pr(p) + \Pr(\lnot q) & = 1 && \text{per axiom 3} \\ \Pr(p) + 1 - \Pr(q) & = 1 && \text{per proof 1} \\ \Pr(p) + 1 & = \Pr(q) + 1 && \text{add \(\Pr(q)\)} \\ \Pr(p) & = \Pr(q) && \text{subtract \(1\)}. \quad \blacksquare \end{align*} \]